RISK FACTORS OF HOUSING CONDITIONS ON THE TRANSMISSION OF BTA POSITIVE PULMONARY TB DISEASE IN THE PUBLIC HEALTH CENTER KEMARAYA KENDARI - masrin, idham (Perhimpunan Ahli Epidemiologi Indonesia, 2024)
Background: TB is an infectious disease caused by mycobacterium tuberculosis. The research aims to analyze the risk factors for the incidence of pulmonary TB at the Kemaraya Kendari Community Health Center. Methods: This study used an observational analytic with a case control design. The sample used was 80 respondents with a total sampling technique.Data was collected through interviews and observations, lighting was measured using a luxmeter. Data were analyzed univariately, bivariately using chisquare, and mutivariately using multiple logistic regression. Results: The data will be analyzed using the chi-square test with the results showing that there is a significant relationship between length of contact (pvalue = 0.004), lighting (p-value = 0.0005) and bedroom (p-value = 0.0005). While the variable that has no significant relationship is gender (p-value = 0.896). Conclusion: Insidence of TB was related to length of contact, lighting, and bedroom.